2006
DOI: 10.3122/jabfm.19.5.494
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Alcohol-exposed Pregnancies

Abstract: Fetal alcohol exposure affects approximately 1% to 3% of live births in the United States. Family physicians are in a unique position to reduce the incidence of alcohol-exposed pregnancy. Fetal alcohol exposure can be minimized through 2 general approaches: reducing alcohol consumption or increasing effective contraception among childbearing-aged women who engage in "at-risk" drinking and encouraging pregnant women to abstain from alcohol. Although no safe level of alcohol consumption during pregnancy is estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 74 publications
3
37
0
Order By: Relevance
“…Most variables that we found to be associated with being at risk of an AEP are similar to those identified previously (e.g., Mengel et al, 2006;Project Choices Research Group, 2002). However, unlike other studies, we did not find mental and physical health perceptions to be significantly associated with being at risk of an AEP.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Most variables that we found to be associated with being at risk of an AEP are similar to those identified previously (e.g., Mengel et al, 2006;Project Choices Research Group, 2002). However, unlike other studies, we did not find mental and physical health perceptions to be significantly associated with being at risk of an AEP.…”
Section: Discussionsupporting
confidence: 82%
“…Religiosity was identified as a protective factor. These maternal risk and protective factors for FAS are not dissimilar to the factors associated with being at risk of an AEP that have been identified in other parts of the world (Mengel, Searight, & Cook, 2006;Project Choices Research Group, 2002).…”
mentioning
confidence: 75%
“…51,52 For example, several studies have already identified factors that increase the risk of alcohol use during pregnancy, including low (SES), having an early age of drinking onset, being unmarried, and reporting heavy drinking by male partner. [53][54][55][56][57] It may be that screeners using indirect risk factors, such as 1522 TZILOS ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Women of lower SES, and women who currently smoke, may also benefit from screening and brief interventions in the clinical setting. 11 Further research into high-risk drinking among women, and prevention strategies, are urgently required in South Africa.…”
Section: Discussionmentioning
confidence: 99%